Atypical Central Neurocytoma: a case report from Ecuador - Fuenmayor, Luis (Revista Argentina de Neurocirugía, 2021)
Central Neurocytoma is a rare benign tumor of the Central Nervous System that mainly affects young adults. Clinically, it manifests with headache, nausea, vomiting, and visual disturbances due to intracranial hypertension. To establish the diagnosis, the use of imaging, histopathology, and immunohistochemistry is necessary. The treatment of choice is total surgical resection, accompanied in selected cases of radiotherapy and chemotherapy. The prognosis that generally is good, depends on the percentage of surgical resection and the characteristics of the tumor. We present the case of a 22-year-old patient with an atypical intraventricular Central Neurocytoma who underwent a subtotal resection and received concurrent chemotherapy and radiotherapy as adjunctive therapy. In the follow up 6 months after the intervention, the patient presented a favorable clinical and neurological evolution.